PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS TUNADAKSA (DISABILITAS FISIK) DI SEKOLAH DASAR - Isti’ana; Liftiah; Ali Formen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Children with physical disabilities (tunadaksa) require educational services that are adaptive, inclusive, and responsive to their physical and psychological needs. This article aims to describe the characteristics, challenges, and educational strategies for children with physical disabilities in elementary schools. The method used is a literature review from various books, journals, and educational regulations related to inclusive education and special needs education. The results show that children with physical disabilities generally experience difficulties in mobility, limitations in the function of limbs, slower movement, difficulties in self-care activities, and decreased self-confidence due to physical differences. Therefore, schools need to provide accessible facilities, adaptive learning methods, emotional support, and inclusive social environments. Teachers also play an important role in fostering students’ confidence and independence through collaborative and student-centered learning approaches. Proper educational support can help children with physical disabilities develop their academic potential, social skills, and self-confidence optimally.